Caracterização socioeconômica e estudo da valoração dos quintais rurais no município de Marituba, PA - Silva, Josiane Santos da (2019)
In the context where one can perceive the great clusters of cities problems related to reduced space, urban swelling, environmental degradation; pollution of soil, water and air, and social problems of income and food distribution, insecurity and unemployment, we seek alternatives that generate a new profile for urban and / or peri-urban areas. In this context, Urban Agriculture is the theme of study of this dissertation, practiced in the backyards of the municipality of Marituba, State of The general objective of the research was to characterize the productive yards in the municipality, as well as valuing its economic, environmental, social and cultural services. O specific objectives were focused on observing biodiversity in backyards; socio-economic profile of the farmers and to investigate how they contribute to for reproduction of the family unit; identify and characterize their relationships with the capital, Belém, and neighboring municipalities, with the intention of knowing their main obstacles to trade in agricultural products and which crops are produced in the yards, thus permeating possible Public Policies that value and family and urban and peri-urban agriculture in the region. The methodology was used to collect data through a questionnaire in 22 quintals. of the sample was based on the Snowball sample format or "Snowball". The Method of Contingent Valuation was used for the study of the valuation of yards, based on in the Acceptable Disposition (DAA). Through a descriptive analysis of the data, it was observed that farmers are aging, however, with few income options, even in the case of retirement and / or other government benefits, mainly due to the lack of access to information. Another result concerns the low frequency of sustainable practices carried out by the producers, which may be an indication of the precarious participation of environmental institutions or of technical assistance in the daily life of the interviewees. The valuation of productive yards simulated an AAR of R $ 2,460.00, which may be justified by the fact that a fixed income is obtained, since the farmers are aging and have difficulty receiving the retirement aid. household income. Considering the results of the research and based on the presented scenario, the social and economic importance of the backyards for the municipality studied is perceptible and, therefore, future works that contribute to the regional development are indicated, through researches involving the study of the urban and / or periurban agriculture relations and their impacts on city food, in order to verify the nutritional influence of productive farms and the impact of the intensive use of pesticides and the landfill in this context.